Photoinduced in situ generation of DNA-targeting ligands: DNA-binding and DNA-photodamaging properties of benzo[c]quinolizinium ions - Schlosser, Julika; Fedorova, Olga; Fedorov, Yuri; Ihmels, Heiko (Beilstein Journal of Organic Chemistry, 2024)
The photoreactions of selected styrylpyridine derivatives to the corresponding benzo[c]quinolizinium ions are described. It is shown that these reactions are more efficient in aqueous solution (97–44%) than in organic solvents (78–20% in MeCN). The quinolizinium derivatives bind to DNA by intercalation with binding constants of 6–11 × 104 M−1, as shown by photometric and fluorimetric titrations as well as by CD- and LD-spectroscopic analyses. These ligand–DNA complexes can also be established in situ upon irradiation of the styrylpyridines and formation of the intercalator directly in the presence of DNA. In addition to the DNA-binding properties, the tested benzo[c]quinolizinium derivatives also operate as photosensitizers, which induce DNA damage at relative low concentrations and short irradiation times, even under anaerobic conditions. Investigations of the mechanism of the DNA damage revealed the involvement of intermediate hydroxyl radicals and C-centered radicals. Under aerobic conditions, singlet oxygen only contributes to marginal extent to the DNA damage.
Keywords: DNA intercalators; heterocycles; photocyclization; photosensitizer; styrylpyridines